M_KEY – Management as a key driver of energy performance - (:unkn) unknown (My University, 2025)
In many companies there are still considerable potentials to reduce energy consumption. Measures to be taken to tap these potentials generally require investing in new equipment. Yet, energy-efficiency (EE) investments - even when highly profitable - remain often undecided. Many studies have identified and discussed the various market and organizational barriers, that hamper decisions, and hence investments, in EE. The proposed research project bases on a new model of decision-making that leads to re-designing the organizational barriers model and to proposing a new explanation of the energy-efficiency gap. According to this new approach, two “meta-barriers” encompass symptom barriers and actually explain the energy-efficiency gap: The perceived non-strategic character of energy-efficiency investments and the various cultural influences which drive organizations and their decision makers to consider energy-efficiency investments as weakly strategic, beyond possible objective reasons. The main research hypothesis is that energy management (e.g. established in the form of an energy management system based on ISO 50001) significantly raises the companies’ ability to perceive the strategic relevance of energy-efficiency investments. Thus energy management induces positive decisions regarding these investments and, ultimately, increases the energy performance of a firm. The project aims at analysing the impacts of energy management as a driving factor in this process through a mix of survey, interviews and case studies among Swiss large-scale energy consumers. The results of the research work should help to better understand the determinants of energy-efficiency investments. This, in turn, will allow conceiving and proposing adequate policy measures and regulations able to improve the energy performance of firms.
Keywords: energy efficiency of firms